2005
DOI: 10.1177/0013164404267293
|View full text |Cite
|
Sign up to set email alerts
|

Employment-Related Motivational Distortion: Its Nature, Measurement, and Reduction

Abstract: The behavioral variable employment-related motivational distortion (EMD) was defined and measured. In Study 1, a sample of 250 undergraduates completed the California Psychological Inventory (CPI), Form 434, on two separate occasions in which they responded (a) honestly and (b) as if applying for a job they valued. Four different change measures indexed participants' response changes between the two conditions on a CPIbased scale measuring counterproductivity (CPI-Cp). A composite of these four measures provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Faking on personality inventories is likely to substantially decrease the criterion-related validity for jobs in which faking may reasonably be expected to be detrimental to some aspects of job performance (i.e., in contexts where the traits that lead to successful faking will interfere with effective work-related behaviors, or encourage ineffective ones). Hakstian and Ng (2005) found that a measure of faking was negatively associated with job performance behaviors for a sample of telephone service representatives and was positively associated with counterproductive behaviors for a sample of armored car company employees. Furthermore, studies have found that individuals identified as fakers perform worse than do individuals identified as nonfakers, in both field (Rosse et al, 1999) and lab settings (Donovan, Dwight, & Schneider, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Faking on personality inventories is likely to substantially decrease the criterion-related validity for jobs in which faking may reasonably be expected to be detrimental to some aspects of job performance (i.e., in contexts where the traits that lead to successful faking will interfere with effective work-related behaviors, or encourage ineffective ones). Hakstian and Ng (2005) found that a measure of faking was negatively associated with job performance behaviors for a sample of telephone service representatives and was positively associated with counterproductive behaviors for a sample of armored car company employees. Furthermore, studies have found that individuals identified as fakers perform worse than do individuals identified as nonfakers, in both field (Rosse et al, 1999) and lab settings (Donovan, Dwight, & Schneider, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…A number of labels have been applied to the phenomenon of individuals applying answers to personality questionnaires that are not commensurate with their actual answers including: impression management (IM), socially desirable responding, response style, response distortion, intentional distortion, and faking (Edens, 2005;Edens et al, 2001;Hakstian and Ng, 2005;Marshall et al, 2005;McFarland and Ryan, 2000). These distinctions in nomenclature have not been substantive -they all basically refer to the same substantive phenomenon.…”
Section: Faking On Personality Inventoriesmentioning
confidence: 99%